2008
DOI: 10.1186/1471-2431-8-45
|View full text |Cite
|
Sign up to set email alerts
|

Childhood osteomyelitis-incidence and differentiation from other acute onset musculoskeletal features in a population-based study

Abstract: Background: Osteomyelitis can be difficult to diagnose and there has previously not been a prospective approach to identify all children in a defined geographic area. The aim of this study was to assess the annual incidence of osteomyelitis in children, describe the patient and disease characteristics in those with acute (< 14 days disease duration) and subacute osteomyelitis (≥ 14 days disease duration), and differentiate osteomyelitis patients from those with other acute onset musculoskeletal features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
113
1
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(139 citation statements)
references
References 44 publications
8
113
1
9
Order By: Relevance
“…The most common etiology in children is hematogenous infections. Previous studies from Norway 32,33 and Lithuania 34 have noted an annual incidence of approximately ten to fourteen cases of hematogenous osteomyelitis per 100,000 children. On the other hand, a lower incidence of acute hematogenous osteomyelitis has been reported in Scotland in two separate studies of the Glasgow population between 1970 and 1997, with an annual incidence of 2.9 new cases per 100,000 population 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…The most common etiology in children is hematogenous infections. Previous studies from Norway 32,33 and Lithuania 34 have noted an annual incidence of approximately ten to fourteen cases of hematogenous osteomyelitis per 100,000 children. On the other hand, a lower incidence of acute hematogenous osteomyelitis has been reported in Scotland in two separate studies of the Glasgow population between 1970 and 1997, with an annual incidence of 2.9 new cases per 100,000 population 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Subacute OM appears to be have increased in recent years, 10 and is reported to be 5 per 100,000 children in Norway. 11 Neonatal infection can occur in preterm or term-born babies and is associated with a wider range of causative organisms (see below) 12 and potential complications. Neonatal vascular anatomy allows infection within the bone to reach the growth plate or joint in 76% of neonatal osteomyelitis cases.…”
Section: Osteomyelitis and Septic Arthritis In Childrenmentioning
confidence: 99%
“…Infection typically occurs in children, and is commonly caused by invasion of the richly vascularized metaphyseal region of the tibia, femur, or humerus by a single microorganism (Claro et al, 2011). Previous studies have suggested that the frequency of acute osteomyelitis is higher in children in Saudi Arabia than in other parts of the world (Blyth et al, 2001;Riise et al, 2008;Al Hajry et al, 2012).…”
Section: Introductionmentioning
confidence: 99%